Communication Disorders in Turkish. - Topbas, Seyhun (Communication Disorders Across Languages, No. 4, 2010)
Deals with Turkish communicative development and disorders, reflecting the use of Turkish by a sizeable population in multilingual settings in Europe, USA, and Australia. This book offers information about the profession of speech-language pathology, cultural differences, assessment materials and research done in communication disorders in Turkey.